The State, Class Struggle, and Capitalist Development in Indonesia and South Korea: A Marxist View - Ridha, Muhammad (Jurnal Politik Indonesia: Indonesian Political Science Review, 2018)
This paper aims to understand why similar efforts of state intervention can generate different economic outcomes. It argues that the different economic outcomes of state intervention can be traced back to the different processes of class struggle. Mobilizing Marxist view, it suggests that the state role in the economy should be understood as inseparable from capitalist development. That is, economic development is the terrain for class struggle between capital and labor. Although the contradictory relation between capital and labor is universal and global in capitalism, the form of contradiction will always be different across societies. That is the case because the form of class struggle depends on the specific development of the configuration of class power that has developed historically in each country alongside with its international process due to the expansive nature of capitalism itself.